SN50, a Cell-Permeable Inhibitor of Nuclear Factor-κB, Attenuates Ventilator-Induced Lung Injury in an Isolated and Perfused Rat Lung Model. Issue 2 (August 2016) - Chian, Chih-Feng; Chiang, Chi-Huei; Chuang, Chiao-Hui; Liu, Shiou-Ling; Tsai, Chen-Liang
Abstract : ABSTRACT: High tidal volume (VT ) ventilation causes the release of various mediators and results in ventilator-induced lung injury (VILI). SN50, a cell-permeable nuclear factor-κB (NF-κB) inhibitory peptide, attenuates inflammation and acute respiratory distress syndrome. However, the mechanisms associated with the effects of SN50 in VILI have not been fully elucidated. We investigated the cellular and molecular mechanisms for the effects of SN50 treatment in VILI. An isolated and perfused rat lung model was exposed to low (5 mL/kg) or high (15 mL/kg) VT ventilation for 6 h. SN50 was administered in the perfusate at the onset of the high-stretch mechanical ventilation. The hemodynamics, lung histological changes, inflammatory responses, and activation of apoptotic pathways were evaluated. VILI was demonstrated by increased pulmonary vascular permeability and lung weight gain, as well as by increased levels of interleukin (IL)-1β, tumor necrosis factor (TNF)-α, myeloperoxidase (MPO), hydrogen peroxide, and macrophage inflammatory protein-2 in the bronchoalveolar lavage fluid. The lung tissue expression of TNF-α, IL-1β, mitogen-activated protein kinases (MAPKs), caspase-3, and phosphorylation of serine/threonine-specific protein kinase (p-AKT) was greater in the high VT group than in the low VT group. Upregulation and activation of NF-κB was associated with increased lung injury in VILI. SN50 attenuated the inflammatory responses, including the expression of IL-1β, TNF-α, MPO, MAPKs, and NF-κB. In addition, the downregulation of apoptosis was evaluated using caspase-3 and p-AKT expression. Furthermore, SN50 mitigated the increases in the lung weights, pulmonary vascular permeability, and lung injury. In conclusion, VILI is associated with inflammatory responses and activation of NF-κB. SN50 inhibits the activation of NF-κB and attenuates VILI.